Academic integrity at ICM: Successes, challenges and opportunities - Gomes, Lincoln; Goncharova, Daria (Canadian Perspectives on Academic Integrity, 2021)
At International College of Manitoba (ICM), we recognized that the stress to students and instructors caused by COVID-19 presented a unique opportunity to raise the awareness of academic integrity in fully online learning. In this presentation we describe several strategies which we employed to mitigate an expected rise in academic misconduct allegations. Strategies were chosen based on reportage from academic literature. Using data collected over two full terms of online learning, we provide insights into emerging trends related to academic integrity and offer a summary of future work in order to improve our performance. We welcome constructive commentary from the audience during question time.